2004
DOI: 10.1016/j.topol.2004.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Tightness, character and related properties of hyperspace topologies

Abstract: Given a Hausdorff space X, we calculate the tightness and the character of the hyperspace CL∅(X) of X, endowed with either the co-compact or the lower Vietoris topology, and give some estimates for the tightness of CL∅(X), endowed with the Fell topology.\ud \ud Some properties related to first-countability and countable tightness, such as sequentiality, Fréchet property and, less directly, radiality and pseudoradiality, are investigated as well.\ud \ud To carry out our investigation, we also consider on the ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 18 publications
1
23
0
Order By: Relevance
“…2 Indeed, on the one hand, this will cause no real loss of generality, because of the equality (that we have just pointed out): τ + Δ = τ + Δ∪{∅} for any Δ ⊆ CL ∅ (X). On the other hand, assuming ∅ ∈ Δ allows us to write a generic τ + Δ -basic neighbourhood of a given C ∈ CL ∅ (X) in the form (D c 1 ) + ∩ · · · ∩ (D c n ) + , where D 1 , .…”
Section: Hyperspacesmentioning
confidence: 94%
See 2 more Smart Citations
“…2 Indeed, on the one hand, this will cause no real loss of generality, because of the equality (that we have just pointed out): τ + Δ = τ + Δ∪{∅} for any Δ ⊆ CL ∅ (X). On the other hand, assuming ∅ ∈ Δ allows us to write a generic τ + Δ -basic neighbourhood of a given C ∈ CL ∅ (X) in the form (D c 1 ) + ∩ · · · ∩ (D c n ) + , where D 1 , .…”
Section: Hyperspacesmentioning
confidence: 94%
“…In a recent paper [2], Costantini, Holá and Vitolo work with the least infinite cardinality of a complete system; consistently with the result of Frolík, they call such a cardinal function theČech number (see also [1]). …”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Most of the results of this section are already known in the case in which X is a Hausdorff space-see [3,5,6,12,14].…”
Section: Axioms Of Countabilitymentioning
confidence: 94%
“…According to a result from [18], each compact Hausdorff space of countable tightness is a Pytkeev space. On the other hand, in [12] (see also [4]) it was shown that for a locally compact Hausdorff space X the tightness of (2 X , F) is countable if and only if X is hereditarily separable and hereditarily Lindelöf. So we have:…”
Section: The Pytkeev Propertymentioning
confidence: 99%